Fatigue behavior and calculation methods of high strength steel fiber reinforced concrete beam - Gu, Zhiqiang; Feng, Hu; Gao, Danying; Zhao, Jun; Wei, Congjie; Wu, Chenglin (Sustainable structures, 2023)
Adding steel fibers into concrete was considered as one of the most effective ways to restrain the crack development and improve the stiffness for reinforced concrete (RC) structures. To explore the reinforcement mechanism of steel fibers on the fatigue behavior of high-strength RC beam, eight high-strength steel fiber reinforced concrete (HSSFRC) beams subjected to fatigue loading were tested in this study. The main design parameters considered in this work were stress level and steel fiber content. The failure mode, crack patterns, fatigue life, crack width, and stiffness degradation of HSSFRC beams under fatigue loading were discussed. The results showed that steel fibers could significantly increase the fatigue life, restrain crack development, and improve crack patterns of HSSFRC beams under fatigue loading compared to ordinary RC beams. Both the crack width and stiffness degradation rate of beams decrease with increasing steel fiber content. Besides, the empirical formulas for calculating the maximum crack width and midspan deflection of HSSFRC beam under fatigue loading were proposed and validated using experimental results.